DRAWING MEDIA TO IMPROVE STUDENTS’ UNDERSTANDING ON PREPOSITIONS - Saragih, Susi Tresya; Riyadi, Slamet; Kariadi, Mustasyfa Thabib (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2022)
Drawing is one of interesting media for teaching and learning processes. When communicating in both spoken and written forms, each speaker must well master the English grammar as one of important linguistic components. This research aimed to reveal the students’ perception on drawing aSs media used to understand preposition and figure out whether or not drawing media can improve the students’ understanding on prepositions. This research was a case study with qualitative research approach. The research was conducted at SMP Muhammadiyah 3 Purwokerto. The research population was 24 Grade VII C students selected using a total sampling technique. The data were collected using observation, test, interview, and questionnaire. The collected data were then selected and displayed based on the research objectives. To validate the data, the researcher used a triangulation method. The research results showed that (1) most students (91.6%) agreed that drawing media were fun and interesting; (2) Drawing Media could improve the students’ understanding on preposition as proven with the average score in pre-test was 61.9, while in post-test was 86.58.